Effectiveness of Conventional and Syariah Monetary Policy Transmission - Yoghi Citra Pratama (Institute for Research and Community Empowerment (LPPM TAZKIA), 2013)
Objective - The purpose of this study is to compare the effectiveness of monetary policy transmission through conventional and Islamic instruments through the interest rate channel and profit loss sharing / margins channel, to control the price level (inflation) and economic growth (output)Method – Methodology used in this study is the Vector Auto Regressive (VAR) / Vector Error correction model (VECM) to see the effect of shock and long-term effects on inflation and output. Variables used are sbi interest rates, PUAB interest rate, deposit rates and lending rates, as well as from the Islamic side is SBIS yield, yield PUAS, profit lost sharing for the deposits and margin financing. This study use Unit Root Test, Cointegration degree of integration test, test causality, VECM and IRF estimates. Using monthly time series data from 2009 s / d 2012.Result – Results of the study showed that the test based on Granger causality, overall, the transmission channel of monetary policy according to the conventional theory, while the monetary policy transmission channel Sharia can not be clearly identified and disconnected in yield / profit and loss sharing deposits. And based on the estimated VECM is known that in the long term Islamic instruments is the right instrument to control inflation.Conclusion – This finding concluded that syariah instruments is the effective instrument in reducing inflation rate and also encourage the growth of Islamic banking, and should also consider the right margin level to increase the output on real sector. Keywords : Monetary Transmission, Central Bank, Industrial Production Index, Consumer Price Index